2021
DOI: 10.3390/molecules26113465
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Studies in Perfundates and Homogenates of Isolated Porcine Kidneys after Flushing with Zinc or Zinc–Prolactin Modified Preservation Solution Using a Static Cold Storage Technique

Abstract: Zinc is an effective anti-inflammatory and antioxidant trace element. The aim of this study was to analyse the protective effect of zinc and zinc–prolactin systems as additives of preservation solutions in the prevention of nephron damage caused during ischemia. The study used a model for storing isolated porcine kidneys in Biolasol®. The solution was modified with the addition of Zn at a dose of 1 µg/L and Zn: 1 µg/L with prolactin (PRL): 0.1 µg/L. After 2 h and 48 h of storage, the levels of alanine aminotra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…We have shown that prolactin (PRL, dose: 1 µg/L) [51,57], lutropin (LH, dose: 0.01 µg/L) [58], and selenium (Se 4+ , dose: 1 µg/L) [48] have a beneficial protective effect on the kidneys. The addition of Zinc to the Biolasol composition at a dose of 1 µg/L showed minor effectiveness in the protection of nephrons [59].…”
Section: Discussionmentioning
confidence: 93%
“…We have shown that prolactin (PRL, dose: 1 µg/L) [51,57], lutropin (LH, dose: 0.01 µg/L) [58], and selenium (Se 4+ , dose: 1 µg/L) [48] have a beneficial protective effect on the kidneys. The addition of Zinc to the Biolasol composition at a dose of 1 µg/L showed minor effectiveness in the protection of nephrons [59].…”
Section: Discussionmentioning
confidence: 93%
“…After this time, the kidney lavage was repeated (0 and 30 min perfusion 2). Markers for indirect assessment of renal function were determined in the perfusate samples collected [ 1 , 2 , 3 ]. After a time of 48 h and 30 min, graft samples were taken for biochemical analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Renal ischemia in the peri-transplant period causes a number of changes that adversely affect the initiation of normal vital functions in grafts after transplantation. The mechanism of ischemic damage has been described in our previous articles [ 1 , 2 ]. The key point is that ischemia causes a rapid depletion of intracellular reserves of high-energy compounds (ATP).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The concentration of malondialdehyde decreased, with a concomitant increase in the antioxidation capacity of plasma [ 48 , 49 ]. Ostróżka-Cieślik et al [ 21 ] also conducted studies on the effect of zinc on the prevention of ischemic damage in isolated porcine kidneys. They modified Biolasol liquid with the addition of Zn at a dose of 1 µg/L and Zn: 1 µg/L with prolactin (PRL): 0.1 µg/L.…”
Section: Antioxidants With a Potential Nephroprotective Effectmentioning
confidence: 99%